Programmatic Management of Drug Resistant Tuberculosis: A New Chapter in The Strategy of Revised National Tuberculosis Control Programme of India - Dixit, Anil K; Chaudhary, Eema; dixit, Jagdamba (National Journal of Community Medicine, 2013)
Emergence of resistance in Mycobacterium tuberculosis against anti-tubercular drugs particularly multidrug-resistant tuberculosis (MDR-TB) has become a significant public health problem in many of the developing countries including India. Although rate of MDR-TB is relatively low in India but largest number of cases in the country pose a big challenge. As per WHO estimates 99,000 cases of MDR TB emerged in India in 2009, out of which 64,000 had been the cases earlier notified to Revised National Tuberculosis Control Programme (RNTCP). A prevalence of about 3 percent is reported in new cases and 12-17 percent in re-treatment cases in different studies countrywide. Under RNTCP, the programme earlier run as DOTS plus has been revised recently and changed to PMDT (Programmatic Management of Drug Resistant Tuberculosis) to make it more user friendly and practical, leaving no scope for development of further resistance and prevent transmission of drug resistant bacilli. Specific measures are being taken with in the Revised National Tuberculosis Control Programme of India to address the MDR-TB problem through appropriate management of patients and strategies to prevent the propagation and dissemination of MDR-TB. The programme already implemented successfully in Delhi state, is planned to be followed throughout the country in its three phases A, B and C in each state to provide cover to different categories of MDR-TB cases.